Desafios comuns, enfrentamentos singulares: narrativas de jovens docentes iniciantes no ensino médio público - Alida Angelica Alves Leal (2017)
This study focused on the experience of young beginner teachers at public high schools in the Belo Horizonte area, generally aiming at identifying which common challenges are the most acute for them and to understand how these individuals face them.Subjects up to the age of 29 were considered as young, and beginner teachers were those subjects with 5 years or less of teaching experience. This investigations methodological course was organized in three phases, involving the collection of statistical data about teachers in the public high-school system (PNAD/2013, School Census /2013, SEE/2015), the application of questionnaires and narrative interviews with 25 young beginner teachers who taught in public schools of said educational modality in a Belo Horizonte, Minas Gerais regional. The empirical material was analyzed from a few analytical categories of the Sociology of the Individual (Martuccelli, 2007, 2010; Araújo and Martuccelli, 2012; Martuccelli and Singly, 2012), of the Sociology of Experience (Dubet, 1994, 1998), and of Sociology of Education (Fanfani, 2005). The study revealed, among other aspects, the existence of joviality marks among Brazilian public highschool teachers, which relate to the following dimensions: territorial distribution, aspects of age, initiation to teaching, schooling, gender, working conditions, income and family conditions. Furthermore, two more acute common challenges faced by young beginner teachers that were studied were identified, which were: the entry and survival in the job market and also, the relationships with young students and co-workers, called inaugural challenges of young teachers. They connect, strive, go throughand areovercomeby various other challenges being uniquely faced by the individuals